Predisposing Factors of Difficult Tracheal Intubation Among Adult Patients in Aliabad Teaching Hospital in Kabul, Afghanistan – A Prospective Observational Study - Oria, Mohammad Sharif; Halimi, Sultan Ahmad; Negin, Fahima; Asady, Abdullah (International journal of general medicine, 2022)
Airway management may be a considerable challenge for anesthesiologists. Currently used preoperative screening tests are known to lack sufficient specificity and sensitivity. Nevertheless, preoperative screenings and the combination of various tests are highly recommended to reduce the risk of unexpected difficult or failed airway management. This study aims to determine if socio-demographic characteristics can predict difficult intubation among adult patients scheduled for elective surgeries under general anesthesia in Aliabad Teaching Hospital, Kabul, Afghanistan. A total of 341 patients were selected based on consecutive sampling method. Informed consent forms were obtained before inclusion in the study. Data were collected using a data collection form. Age, gender, ASA physical status and ethnicity were recorded for each participant. Airway assessment tests such as mouth opening (MO), thyromental distance (TMD), and Mallampati classes, inability to prognath (AP) and neck mobility and size (NM) category were conducted by research team. Data were initially entered into an Excel data sheet and then exported to SPSS Statistics version 22 for analysis. From 28 October 2018 to 30 January 2019, a total of 341 patients included in the study. Of these, 193 (56.6%) were male and 148 (43.4%) were female. The mean age of the subjects was 36.98 ± 15.048 years. More than half (54.5%) of the study population were Tajiks. Patients from the Hazara ethnicity, female patients, older patients and those suffering from systemic diseases found to be more difficult to intubate. We recognized that, Mallampati classes ≥3, small MO, short TMD, AP, reduced NM were also associated with difficult intubation. Multiple logistic regression analysis of the associated factors determined that increased age more than 40 years, AP and small MO were independent predictors of difficult intubation. The study findings show that Hazara ethnicity, female patients, increasing age and systemic disease have significant associations with difficult intubation. Mallampati classes III and IV, MO ≤4 cm, TMD ≤6 cm, and reduced NM had higher risks of difficult intubation. Multiple logistic regression analysis determined that increased age, AP and MO were independent predictors for difficult intubation.